Dynamic Behaviour of Back to Back Planetary Gear in Run Up and Run Down Transient Regimes. (11th August 2015) - Hammami, A.; Rincon, A. Fernandez Del; Chaari, F.; Rueda, F. Viadero; Haddar, M.
Abstract : The operating cycle of planetary gear transmissions is composed by the run up regime, steady state regime with fixed speed and the run down regime. Run up and run down are one of the main non stationary excitations for planetary gearboxes. This paper investigates, in these two regimes, the dynamic behaviour of a special configuration of two stages planetary gear which are mounted back-to-back. A dynamic model is developed. The variability of speed in the run up and run down regimes is included in the model. The computation of the dynamic response shows that additional sidebands instability zones are generated. Using the Short Time Fourier Transform, an amplitude-frequency modulation is observed in the non stationary condition. An experimental study done on a back-to-back planetary gear test rig is conducted for validation of the mathematic model.